2019
DOI: 10.1016/j.bbr.2018.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Activation of 5-HT1B receptors in the Lateral Habenula attenuates the anxiogenic effects of cocaine

Abstract: Recent work has implicated the Lateral Habenula (LHb) in the production of anxiogenic and aversive states. It is innervated by all the major monoamine neurotransmitter systems and has projections that have been shown to modulate the activity of both dopaminergic and serotonergic brain regions. Cocaine is a stimulant drug of abuse that potentiates neurotransmission in these monoamine systems and recent research suggests that the drug's behavioral effects may be related in part to its actions within the LHb. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
1
2
0
Order By: Relevance
“…The anxiolytic activity was stopped after the administration of the selective 5-HT 1B antagonist, NAS-181. These results confirm the contribution of this receptor to the effects resulting from cocaine administration and also reaffirm the possibility of making it a target for treatments against anxiety [ 33 ].…”
Section: 5-ht 1 Receptorssupporting
confidence: 75%
“…The anxiolytic activity was stopped after the administration of the selective 5-HT 1B antagonist, NAS-181. These results confirm the contribution of this receptor to the effects resulting from cocaine administration and also reaffirm the possibility of making it a target for treatments against anxiety [ 33 ].…”
Section: 5-ht 1 Receptorssupporting
confidence: 75%
“…Raphe serotonergic neurons project to various brain regions implicated in anxiety, depression and drug addiction, including the habenula (Hb) (Metzger et al, 2017;Zhang et al, 2018): a serotonergic circuitry, in fact, exists from the dorsal raphe nucleus to the Hb, and from the Hb back to the dorsal raphe nucleus, through the rostral tegmental area and interpeduncular nucleus. The Hb is a small conserved epithalamic structure that has recently received increasing attention in addiction research (Gao et al, 2018;López et al, 2018;Meye et al, 2017;Meye et al, 2015;Zapata et al, 2017) and it contributes to the induction of negative emotional states in drug addiction (Batalla et al, 2017;Klein et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has also indicated that the LHb contributes to the anxiogenic response that occurs with cocaine administration [12]. In an attempt to identify the neurochemical substrates responsible for the behavioral effects of LHb activation, our laboratory has previously focused on the roles of DA and serotonin (5-HT) within the LHb as related to the encoding of anxiogenic events [18,19], but there is reason to believe that norepinephrine (NE) may also play a role [2022].…”
Section: Introductionmentioning
confidence: 99%